The Effect of Pick-up Service Savings on Customer Loyalty of BPRS Bhakti Sumekar Pragaan Branch Office Moderated Customer Satisfaction - Moh. Helmi Hidayat; Kholifatul Hasanah; Iqbal Rafiqi (Universitas Islam Lamongan, 2023)
This research is a quantitative research by using multiple linier regression analysis and interaction analysis (MRA). The method of data collection uses a questionnaire. The goal of this research is to analyze the effect of barokah savings pick-up service and customer satisfaction on customer loyalty of BPRS Bhakti Sumekar Pragaan Branch Office. It also analyzes the relation of barokah savings pick-up service on customer loyalty of BPRS Bhakti Sumekar Pragaan Branch Office moderated by customer satisfaction. The results of multiple linear regression analysis show that the p-value of the pick-up service variable is 0.111 > 0.05, and customer satisfaction is 0.001<0.05, Based on the results of the MRA test, the p-value of interaction variable between the pick-up service and customer satisfaction is 0.009 < 0.05. These results mean that the barokah savings pick-up service has no significant effect on customer loyalty at BPRS Bhakti Sumekar, customer satisfaction has a significant influence on customer loyalty BPRS Bhakti Sumekar Pragaan Branch Office. Customer’s satisfaction, however, can moderate the interaction between the savings pick-up service and customer loyalty. Thus, for increasing customer loyalty on the firm, the employees have to pay attention to the service provided and try to provide it according to what is communicated to the costumers.